Modelling to support land and water management: experiences from the Mekong River Delta, Vietnam - Hoanh, Chu Thai; Phong, N.D.; Trung, N. H.; Dung, L.C.; Hien, N. X.; Ngoc, N.V.; To Phuc Tuong (Informa UK Limited, 2012)
By comparing the successful story of a hydrodynamic model (based on its contribution to policy changes, management options and livelihood improvement) with other modelling cases in the Mekong River Delta, five success factors are identified. These are (1) simulated phenomena relevant to and understandable by policy makers; (2) response to the needs of policy setting; (3) developed and handled by national modellers with direct links to the policy process; (4) availability of input data; and (5) long application history. These success factors provide higher opportunities for engaging modelling activities with policy setting.